A rational design of multiple-layer films with continuous impedance gradient variation for enhanced microwave absorption. Issue 7 (31st January 2023) - Quan, Bin; Wang, Yu; Chen, Yu; Zhang, Mingji; Liu, Jun; Jia, Qi; Lu, Xiaochi; Chen, Jun; Huang, Xiaogu
Abstract : Multiple-layer films with impedance matching gradient have been fabricated in this work to be applied as wearable and portable devices for micowave absorption. Abstract : Electromagnetic (EM) wave absorption films have attracted considerable attention for their wearable, portable features and easy replacement of damaged parts. Due to the lack of structural design, common EM wave absorption films are limited to narrow bandwidth and poor adjustability. Therefore, designing and constructing the EM wave-absorbing film with good IM characteristics and EM response are the keys to developing high-efficiency EM wave-absorbing films. In this study, computer simulation technology was first used to simulate and predict the absorbing properties of the multiple-layer material with impedance matching (IM) gradient. Then, the GO/ZIF-67-based multiple-layer films with continuous composition/IM changes were designed and prepared by simple vacuum filtration assembly and sequentially underwent thermal conversion. The GCo600 samples obtained by heat treatment at 600 °C showed the optimal IM gradient characteristics and absorbing performances (effective bandwidth (RL < −10 dB) coming up to 13.6 GHz), whose outer part was an IM layer dominated by magnetic loss, and the inner parts were gradually converted to rGO dominated by dielectric loss. The designed structure not only realized sufficient EM wave introduction but also dissipated the incident EM energy with gradually increased loss capability. The study of novel multiple-layer films from simulation to experimental validation opens up a new approach for high-efficiency EM wave absorption based on the continuous IM gradient design.